Acute diarrhea with blood: diagnosis and drug treatment - Mara Alves da Cruz Gouveia; Manuela Torres Camara Lins; Giselia Alves Pontes da Silva (Elsevier, 2020)
Objective: To restate the epidemiological importance of Shigella in acute diarrhea with blood, providing an overview of the treatment and stressing the need for the correct indication of antibiotic therapy. Sources of Data: A search was carried out in the Medline and Scopus databases, in addition to the World Health Organization scientific documents and guidelines, identifying review articles and original articles considered relevant to substantiate the narrative review. Synthesis of Data: Different pathogens have been associated with acute diarrhea with blood; Shigella was the most frequently identified. The manifestations of shigellosis in healthy individuals are usually of moderate intensity and disappear within a few days. There may be progression to overt dysentery with blood and mucus, lower abdominal pain, and tenesmus. Conventional bacterial stool culture is the gold standard for the etiological diagnosis; however, new molecular tests have been developed to allow the physician to initiate targeted antibacterial treatment, addressing a major current concern caused by the increasing resistance of Shigella. Prevention strategies include breastfeeding, hygiene measures, health education, water treatment, and the potential use of vaccines. Conclusions: Acute diarrhea is an important cause of mortality in children under 5 years and shigellosis is the leading cause of acute diarrhea with blood worldwide. The current concern is the increase in microbial resistance to the recommended antibiotics, which brings an additional difficulty to therapeutic management. Although no vaccine is yet available against Shigella, several candidates are undergoing clinical trials, and this may be the most cost-effective preventative measure in future. Resumo: Objetivo: Reiterar a importância epidemiológica da Shigella na diarreia aguda com sangue, fornecer uma visão geral do tratamento e ressaltar a necessidade da correta indicação da antibioticoterapia. Fontes dos dados: Realizada pesquisa nos bancos de dados Medline e Scopus, além de documentos científicos e diretrizes da Organização Mundial da Saúde, com a identificação de artigos de revisão e artigos originais considerados relevantes para fundamentar a revisão do tipo narrativa. Síntese dos dados: Diferentes patógenos têm sido associados à diarreia aguda com sangue, a Shigella é o mais frequente. As manifestações da shigelose em indivíduos saudáveis são geralmente de intensidade moderada e desaparecem em poucos dias. Pode haver progressão para disenteria franca com sangue e muco, dor em abdome inferior e tenesmo. A coprocultura bacteriana convencional é o padrão-ouro para o diagnóstico etiológico, porém novos testes moleculares foram desenvolvidos, os quais permitem ao médico iniciar tratamento antibacteriano direcionado, sanar uma grande preocupação atual, devido à crescente resistência da Shigella. Estratégias de prevenção incluem aleitamento, medidas de higiene, educação em saúde, tratamento da água e o potencial uso de vacinas. Conclusões: A diarreia aguda é uma importante causa de mortalidade em crianças com menos de cinco anos e a shigelose é a principal causa de diarreia aguda com sangue em todo o mundo. A preocupação atual é o aumento da resistência microbiana aos antibióticos preconizados, o que traz uma dificuldade adicional ao manejo terapêutico. Embora ainda não exista vacina disponível para Shigella, várias candidatas estão em fase de testes clínicos, podem futuramente ser a medida preventiva mais custo-efetiva. Keywords: Acute diarrhea, Dysentery, Shigella, Treatment, Bacterial resistance, Palavras-Chave: Diarreia aguda, Disenteria, Shigella, Tratamento, Resistência bacteriana